SKOR KEBOCORAN VASKULER SEBAGAI PREDIKTOR AWAL SYOK PADA DEMAM BERDARAH DENGUE - Setiati, Tatty Ermin; Retnaningsih, Anastasia; Supriatna, Mohmad; Soemantri, Agustinus (Jurnal Kedokteran Brawijaya, 2005)
The prediction of shock in Dengue Hemorrhagic Fever is difficult to made, hence, is difficult to detect  shock as early as possible. This results in delayed management and ultimately can cause death. Serum levels of protein, albumin, hematocrit, and PEI which are markers of vascular leakage hoped to be able to be used as predictor of  shock in DHF. The aim of this study was to develop a scoring system, the Vascular Leakage Score (VLS) that could be used as the predictor of shock and to define the probability ofshock from each total score. This was a cross-sectional, observational analytic study, in RSDK, Semarang from 2001-2003. The samples were 138 children with DHF, aged 3-14 years old, divided into 52 cases of DHF without shock, and 76 cases of Dengue Shock Syndrome. Serum levels of protein, albumin, PEI, and hematocrit were obtained at admission. Then, a classification was made upon the four parameters mentioned above, based on the ROC curve analysis from the previous studies, and based on the WHO’s criteria. To develop a formula for VLS, we gave points-weight for each parameter to calculate the β-coefficient, then continued with calculation of DSS probability based on total combination of the four categories above, using a logistic-regression analysis of multivariate.